Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

kaiteDID

  • 3 years ago

Solve the equations by substitution. If the equations are inconsistent and the solution is an empty set, write "no solution". 5 x - 6 y = 0 y = x x = y =

  • This Question is Closed
  1. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    replace \(y\) by \(x\) in the first equation and get \[5x-6x=0\] or \(-x=0\) making \(x=0\) and so \(y=0\) too

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy